Effect of hydrocolloid dressings in the management of different grades of pressure wound ulcers in critically ill adult subjects: A meta‐analysis - Huang, Ruifeng; Hua, Zhaozhao; Li, Lan; Zhou, Yiyuan; Xu, Yuefang; Zhang, Taiwei (International wound journal, 2023)
A meta‐analysis was implemented to appraise the effect of hydrocolloid dressings (HCDs) in the management of different grades of pressure wound ulcers (PWUs) in critically ill adult subjects (CIUSs). Inclusive literature research until April 2023 was done, and 969 interconnected researches were revised. The 8 picked researches, enclosed 679 critically ill adult persons at the utilized researchers' starting point; 355 of them were utilizing HCDs, and 324 were controls. Odds ratio (OR) and 95% confidence intervals (CIs) were utilized to appraise the consequences of HCDs in treating CIUSs by the dichotomous approach and a fixed or random model. HCDs had significantly higher PWU complete healing (OR, 2.15; 95% CI, 1.54–3.02, p < 0.001), PWU stage II ulcers complete healing (OR, 2.82; 95% CI, 1.40–5.69, p = 0.004), and PWU stage III ulcers complete healing (OR, 3.73; 95% CI, 1.23–11.35, p = 0.02) compared to control in critically ill adult persons. HCDs had significantly higher PWU complete healing, PWU stage II ulcers complete healing, and PWU stage III ulcers complete healing compared with control in critically ill adult persons. However, caution needs to be taken when interacting with its values since there was a low sample size of most of the chosen research found for the comparisons in the meta‐analysis.